1994
DOI: 10.1002/ardp.19943270309
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic and Antiviral Activities of Podophyllotoxin Related Lignans

Abstract: 28 cyclolignans, most of them derived from podophyllotoxin, have been evaluated for their antineoplastic and antiviral activities. They were subjected to screening against P-388 murine leukemia, A-549 human lung carcinoma, and HT-29 colon carcinoma, while antiviral assays were performed on herpes simplex virus type I infecting fibroblasts of monkey kidney (HSV/CV-1) and on vesicular stomatitis virus infecting fibroblasts of hamster kidney (VSV/BHK). A number of substances were active in both groups of assays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 15 publications
0
53
0
Order By: Relevance
“…To date, some of the most important studied metabolites are podophyllotoxin and its hemisynthetic derivatives (etoposide, teniposide, and etoposide phosphate), which are particularly interesting due to their ability to inhibit tumor cell proliferation, making them useful in chemotherapy for the treatment of lung cancer (Ayres & Loik, 1990;Gordaliza et al, 2006;Yang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To date, some of the most important studied metabolites are podophyllotoxin and its hemisynthetic derivatives (etoposide, teniposide, and etoposide phosphate), which are particularly interesting due to their ability to inhibit tumor cell proliferation, making them useful in chemotherapy for the treatment of lung cancer (Ayres & Loik, 1990;Gordaliza et al, 2006;Yang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As a promising microtubule inhibitor candidate, DPT possesses various pharmacological activities, including anti-inflammatory (Jin et al, 2008), anti-viral (Gordaliza et al, 1994), anti-angiogenic (Wang et al, 2015a, and anti-tumor effects, among which anti-tumor attracted most attention. Previous studies have shown that DPT inhibits the proliferation of SGC-7901 cancer cells and induces G2/M cell cycle arrest (Wang et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…This group is commonly called as pyrazolignans [19,20,24,25,27] and isoxazolignans [25,26,28,29] and they were obtained by reacting podophyllotoxine with differently substituted hydrazines and hydroxylamines.…”
Section: Virtual Library Designmentioning
confidence: 99%
“…Structural modification mainly introduced varying radicals at position 7 in podophyllotoxin scaffold. Reports have been made of compounds with oxygenated substituents in the form of ethers, esters and diverse nitrogen radicals [17][18][19][20][21][22][23][24][25][26].…”
Section: Virtual Library Designmentioning
confidence: 99%